Total hip arthroplasty in patients with Trisomy 21: Systematic review and exploratory patient level analysis. Issue 1 (February 2019) - Sha, Shiv; Abdelsabour, Hany; Vijimohan, Suganth J.; Board, Tim; Alshryda, Sattar
Abstract: Introduction: Trisomy 21 is the most common chromosomal disorders in humans; it is caused by an extra copy of chromosome number 21. This extra chromosomal material causes widespread abnormalities involving nearly every part of human body. Hip disorders are the second most serious musculoskeletal disorder in patients with T21 with a reported incidence between 2 and 28%. The outcomes of these hip disorders in patients with T21 are much less favorable than similar hip diagnoses in normal patients and a substantive number of these patients develop severe osteoarthritis that require total hip arthroplasty (THA). The outcome of THA in this cohort of patient is not well studied. Methods: A modified Cochrane review methodology has been utilized in this review. An extended literature search was performed of the medical databases. A hierarchical approach was used to include relevant studies. Search, published papers and extracted data were checked by authors independently then jointly to ensure accuracy. Results: Nine studies (321 patients with Trisomy 21) who underwent total hip arthroplasty (THA) were included. The functional hip scores (Harris and WOMAC hip scores) improved substantively after hip arthroplasty. The 5-year cumulative revision rate was 7.5%; twice as high as age matched control. Medical and surgical complications were 3 times higher than matched controls. Conclusion: Total hip arthroplasty can be offered to patients with T21 and severe arthritis although the increased revision and complication rates must be appreciated by patients and care givers.